Symphony No. 9 in D minor: with performing version of the finale by Samale, Phillips, Cohrs, Mazzuca; [four movement version] - Bruckner, Anton and Samale, Nicola and Phillips, John A. and Cohrs, Benjamin Gunnar and Mazzuca, Giuseppe and Rattle, Simon (EMI classics, 2012)
„Seit jeher wird der Blick auf Bruckners Neunte Symphonie, seine "Unvollendete", durch ominöse Mythen- und Legendenbildungen verstellt. Jetzt haben Simon Rattle und seine Berliner Philharmoniker ihre bahnbrechende Neueinspielung um den aktuellsten Rekonstruktionsversuch des nur fragmentarisch überlieferten Finalsatzes erweitert“ (br.de). „For music lovers who discount the validity of any fourth movement to the Symphony No. 9, there is much to enjoy in the Berliner Philharmoniker’s performance of the first three movements: “Mr. Rattle and the Berlin players deftly balanced elements of Schubertian structure and Wagnerian turmoil in the mysterious first movement. The brutal power of the scherzo’s main theme was chilling, with the orchestra pummelling the dense, thick, dissonance-tinged chords. And Mr. Rattle laid out the threads of chromatic counterpoint in an organic, glowing and, when appropriate, gnashing account of the Adagio.” (The New York Times) For those with the intellectual curiosity to hear how accomplished Bruckner scholars have most recently realised the unfinished movement, it is performed here by the world-renowned team of Sir Simon Rattler and the Berliner Philharmoniker“ (prestoclassical.co.uk)
https://katalog.adlr.link/Record/0-1600454275